GROWTH, PLAQUE PRODUCTION, AND CATIONIC STABILIZATION OF RHINOVIRUS TYPE 1 (ECHOVIRUS 28) - Behbehani, Abbas M. (1964)
Behbehani, Abbas M. (Baylor University College of Medicine, Houston, Tex.), and L. H. Lee. Growth, plaque production, and cationic stabilization of rhinovirus type 1 (echovirus 28). J. Bacteriol. 88:1608–1611. 1964.—A variety of conditions for the growth of echovirus 28 were investigated. The virus grew more readily and to the highest titer when secondary MK cells maintained in low bicarbonate and rolled at 33 C were employed. Viral plaques were produced in human diploid (WI-38) cell cultures. The virus was protected from thermal inactivation (50 C for 1 hr) by 1 m MgCl(2). For storage of the virus at refrigerator and room temperature, the use of 1 m MgCl(2) is also of advantage.